2005
DOI: 10.1093/hmg/ddi198
|View full text |Cite
|
Sign up to set email alerts
|

CDKL5 belongs to the same molecular pathway of MeCP2 and it is responsible for the early-onset seizure variant of Rett syndrome

Abstract: Rett syndrome (RTT) is a severe neurodevelopmental disorder almost exclusively affecting females and characterized by a wide spectrum of clinical manifestations. Most patients affected by classic RTT and a smaller percentage of patients with the milder form 'preserved speech variant' have either point mutations or deletions/duplications in the MECP2 gene. Recently, mutations in the CDKL5 gene, coding for a putative kinase, have been found in female patients with a phenotype overlapping with that of RTT. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
253
2
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 288 publications
(270 citation statements)
references
References 37 publications
9
253
2
6
Order By: Relevance
“…12,13 To date, over 200 sequence variants or genomic deletions in CDKL5 have been reported in both female and male patients with X-linked dominant early-onset seizures manifesting before 5 months of age, severe intellectual disability with absent speech, and Rett-like features such as hand stereotypies and deceleration of head growth classified as Epileptic encephalopathy, early infantile, 2 (OMIM 300672) or Angelman syndrome-like (OMIM 105830). 7,[14][15][16][17][18] The phenotypic resemblance to Rett syndrome has been proposed to result from similar functions or interactions between CDKL5 and MECP2 in their molecular pathways during neurodevelopment (OMIM 30005); 4,13,[19][20][21][22][23] however, more studies are needed to verify this hypothesis. Most recently, Livide et al 24 showed that a subunit of glutamate receptor ligand-gated ion channel, GluD1, encoded by GRID1, is a commonly altered player in neuronal differentiation from both MECP2-mutated and CDKL5-mutated iPS cells and suggested that it could be a new therapeutic target for Rett syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 To date, over 200 sequence variants or genomic deletions in CDKL5 have been reported in both female and male patients with X-linked dominant early-onset seizures manifesting before 5 months of age, severe intellectual disability with absent speech, and Rett-like features such as hand stereotypies and deceleration of head growth classified as Epileptic encephalopathy, early infantile, 2 (OMIM 300672) or Angelman syndrome-like (OMIM 105830). 7,[14][15][16][17][18] The phenotypic resemblance to Rett syndrome has been proposed to result from similar functions or interactions between CDKL5 and MECP2 in their molecular pathways during neurodevelopment (OMIM 30005); 4,13,[19][20][21][22][23] however, more studies are needed to verify this hypothesis. Most recently, Livide et al 24 showed that a subunit of glutamate receptor ligand-gated ion channel, GluD1, encoded by GRID1, is a commonly altered player in neuronal differentiation from both MECP2-mutated and CDKL5-mutated iPS cells and suggested that it could be a new therapeutic target for Rett syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have identified large gene deletions in RTT patients that escaped detection by PCR-based screening strategies (Laccone et al 2004;Schollen et al 2003). Others have identified mutations in a novel MeCP2 isoform and in CDKL5 (Archer et al 2006a, b;Evans et al 2005a;Kriaucionis et al 2004;Mari et al 2005;Scala et al 2005;Tao et al 2004;Weaving et al 2004). This study reports the results of the mutation analysis of MECP2 and CDKL5 in 121 unrelated Chinese patients with classic or atypical RTT, conducted to obtain a genotypic representation of the mutational spectrum in this population.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The gene is composed of 20 encoding exons, and so far 450 mutations in patients with CDKL5-related encephalopathy have been reported, affecting quasi-exclusively girls. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Patients with CDKL5 mutations typically present severe intellectual disability and early seizures, microcephaly in B1/3 of cases, as well as RTT-like features such as severe hypotonia, hand stereotypies and sleep disturbances. 22 Several patients having symptoms reminiscent of a CDKL5-related disease profile have had no mutation identified, in spite of the large screening strategy that is available, suggesting that other unexplored regions and/or genetic loci are involved in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…6,23 CDKL5 phosphorylation targets are currently largely unknown. So far, it has been shown that the protein, in vitro, may autophosphorylate, and it phosphorylates the product of the methyl-CpG-binding protein 2 (MECP2, OMIM 300005) gene, which is mutated in 490% of classic RTT patients, 24 suggesting a common signaling pathway between these two proteins; 6,9,25 and the N-terminal region of the DNA methyltransferase 1 in nuclei. 26 In this study, we report the coincidental finding of an additional exon within the CDKL5 gene and describe its conservative feature in several species.…”
Section: Introductionmentioning
confidence: 99%